The Efficacy of Saffron in the Treatment of Mild to Moderate Depression: A Meta-analysis - Tóth, Barbara; Hegyi, Péter; Lantos, Tamás; Szakács, Zsolt; Kerémi, Beáta; Varga, Gábor; Tenk, Judit; Pétervári, Erika; Balaskó, Márta; Rumbus, Zoltán; Rakonczay, Zoltán; Bálint, Emese Réka; Kiss, Tivadar; Csupor, Dezső (Planta Medica, 2019)
Herbal products, especially Hypericum perforatum extracts, have been widely used as first-line treatments for mild to moderate depression. Recently, several randomized, controlled clinical trials have been conducted to evaluate the efficacy of another plant, saffron (Crocus sativus), in mild to moderate depression. We have carried out a literature review of currently available published randomized, controlled clinical trials to give an up-to-date evaluation of the efficacy of saffron in mild to moderate depression, compared to placebo or routinely used antidepressants. The meta-analysis is reported according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines using the PICO (patients, intervention, comparison, outcome) format and was conducted using the statistical programs Comprehensive Meta-analysis and RevMan. PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science databases were searched for relevant studies. Only placebo or active controlled, randomized clinical studies involving patients suffering from mild to moderate depression and using pharmacological doses of saffron per os were included. Hedgesʼ g was used to calculate effect sizes. Risk of bias was assessed using the Cochrane Collaboration tool, and heterogeneity was tested by both performing the Cochranʼs Q test and calculating Higginsʼ I2 indicator. Eleven randomized trials were included in the qualitative analysis, and nine were pooled for statistical analysis. According to the present meta-analysis, saffron has a significant effect on the severity of depression. Available data from randomized, controlled clinical trials support that saffron is significantly more effective than placebo (g = 0.891; 95% CI: 0.369 – 1.412, p = 0.001), and non-inferior to tested antidepressant drugs (g = − 0.246; 95% CI: − 0.495 – 0.004, p = 0.053).
Keywords: saffron; Crocus sativus; Iridaceae; depression; meta-analysis